2020
DOI: 10.1111/jocd.13725
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of chemical peeling as a single agent for melasma in dark‐skinned patients: A systematic review and meta‐analysis of comparative trials

Abstract: Background Chemical peelings are used on a wide scale in cosmetic field including melasma treatment. They often provide clinicians with flexibility in tailoring treatments according to patient needs and satisfaction. Objective To evaluate safety and efficacy of chemical peeling as single agents in melasma management in patients with darker skin types. Methods We included randomized controlled trials (RCTs) and prospective studies that assessed efficacy and safety of chemical peeling as single agents for facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Also, a strong correlation between MASI and Sun Exposure, R = 0.663 (Table 6) was noted in our study. Jointly, studies provide evidence that excessive sun exposure contributes to melasma and therefore impacts the severity of melasma [59][60][61]. The excessive sun exposure from our study may have resulted from the participation in outdoor sports as well as insufficient sun protection application, as indicated by the study respondents.…”
Section: The Use Of Sunscreenmentioning
confidence: 71%
“…Also, a strong correlation between MASI and Sun Exposure, R = 0.663 (Table 6) was noted in our study. Jointly, studies provide evidence that excessive sun exposure contributes to melasma and therefore impacts the severity of melasma [59][60][61]. The excessive sun exposure from our study may have resulted from the participation in outdoor sports as well as insufficient sun protection application, as indicated by the study respondents.…”
Section: The Use Of Sunscreenmentioning
confidence: 71%
“…Te systematic review and metaanalysis of comparative trials by Dorgham et al reported satisfactory results of glycolic acid (GA) and trichloroacetic acid peel as a melasma treatment in dark skin patients, with better efects and safety profle of GA. Undoubtedly, there is a need to perform research evaluating the efectiveness of retinol peel in the population with Fitzpatrick IV-VI skin type [24].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical peeling is the recommended second-line treatment for melasma, and it can accelerate epidermal renewal and collagen regeneration to remove epidermal melanin and suspend the transfer of melanosomes ( 48 ). A systematic review and meta-analysis showed that GA peeling had no obvious advantage over tretinoin (MD 0.00, 95% CI [0.99, 0.99], P = 0.3) and VC (MD 1.50, 95% CI [0.50, 3.50], P = 0.14), while TCA peeling (MD 5.30, 95% CI [6.41, 173 4.19], P < 0.001) and Jessner solution (MD 3.20, 95% CI [5.35, 1.05], P = 0.004) were better than HQ in treating melasma ( 49 ). Chemical peeling in this study included GA, TCA, SA, and Jessen solution.…”
Section: Discussionmentioning
confidence: 99%